Aprendizagem de licenciandas de Matemática a partir das práticas vivenciadas em um grupo de pesquisa educacional - Queiroz, Paulo Henrique (2016)
This research aims to understand the formative experienced by graduate students to participate in studies and research group aimed at the educational practices in mathematics. The research was developed in the group of studies and research on formative and educational practices in mathematics (GEPRAEM) that hosts the project "Collaborative Network of Practices in the training of teachers who teach Mathematics: Multiple perspectives, Dialogue and Contexts" belonging to the Centre for Education (OBEDUC) in network with three universities. This group gathers every two weeks in San Carlos, being made up of future mathematics teachers, basic school teachers, graduate students in education, and a college professor. This research is of qualitative nature of interpretative nature and uses as tools: graduate students productions, audio recordings of the meeting of the group and semi-structured interview. The data analysis was composed by first identifying the various practices developed in the project using the documents of the group, and the second moment, triangulating the data to analyze the perceptions of graduate students on the participation and professional learning teachers in the study group and collaborative investigative research. For these moments of analysis, we used the theoretical framework referential on initial training of teachers in particular, in addition to learning math teachers, the partnership between university and school and research in the initial teachers training. The theoretical foundation of the research considers mainly the initial teacher training (Saviani, 2009; Gatti, 2010), degree in Mathematics (Junqueira and Manrique) , Collaborative Groups (Gama 2007, 2013 and Fiorentini, 2013) and research on training teachers (ANDRÉ, 2009, 2010). The results show that the main group practices (1) Bank of Educational Data Analysis; (2) Production and collective narratives reflection; (3) Productions and Research Project Presentations, Dissertations and Scientific Initiations (4) theoretical and methodological studies. According to the graduate students, these practices provide learning, as improving the scientific academic writing; learn and lose the fear of public speaking; Know the search of the other students, opine and cooperate with the project - and also learn from it; conceiving research as a teacher education; find the research proposed by the group, the desire to become a researcher, academic seeking new opportunities; Prepare, from group studies, Master?s projects and developed skills to work in groups and in collaboration with each other